Law and order in india - Saksena, N. S. (New Delhi, 1987)
In the present book on 'Law and Order in India' Mr. N.S. Saksena has used his field experience of police work for 37 years and later on the knowledge acquired by him as Member, National Police Commission to perform a multi plicity of tasks in this book.
Keywords: Law